Lighting Systems Designed for Energy Savings in Buildings (LSD-ESB): A Review - Al-Ghaili A.M.; Kasim H.; Hassan Z.; Jorgensen B.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Buildings; Lighting; Lighting fixtures; Systems analysis; Cited papers; Elsevier; In-buildings; Lighting systems; Literature reviews; Review papers; Save energy; Energy conservation